Carbazole-based diphenyl maleimides: Multi-functional smart fluorescent materials for data process and sensing for pressure, explosive and pH. (October 2016) - Mei, Xiaofei; Wei, Kexi; Wen, Guixiu; Liu, Zhengde; Lin, Zhenghuan; Zhou, Zhonggao; Huang, Limei; Yang, E; Ling, Qidan
Abstract: A series of carbazole-based diphenyl maleimide dyes with different N-substituent were synthesized through an Ullmann reaction in high yields. The dyes exhibit an intense emission in the solid state for their twisted conformation fixed by weak intermolecular interactions, resulting in the hindrance of the internal rotations. Their solid-stated emission wavelength and intensity are sensitive to external stimuli (like heat, pressure and vapor), due to a crystal-to-crystal or crystal-to-amorphous phase transition. Based on the multi-stimuli-responsive fluorescence properties of the N -benzyl analogue, two kinds of applications were explored. One is rewritable data recording processes including solvent writing and vapor writing. The other is sensing for low hydrostatic pressure (0–25 MPa). Interestingly, nanoparticles of the dyes formed in aqueous solution could effectively detect explosive and pH changes. A 15 ppm concentration of picric acid quenched the fluorescence of the N -methyl analogue with the detectable limit calculated to be 0.13 ppm. The N -methyl analogue also showed a different emission color and intensity over the pH range 12–14, which originated from the hydrolysis of the dye molecules in the strongly basic solution. Graphical abstract: Highlights: A series of diarylmaleimide dyes with different N -substituent were synthesized. Switch from yellow to red emission results from a crystal-to-crystal transition. Piezochromic fluorescence under a low hydrostatic pressure (0–25 MPa) was observed. Rewritable data recording including solvent writing and vapor writing were explored. Nanoparticles of the dyes in aqueous solution can effectively detect picrates and changes in pH.